Beta-sheet containment by flanking prolines : molecular dynamic simulations of the inhibition of beta-sheet elongation by proline residues in human prion protein - S. Shamsir, Mohd.; Dalby, Andrew R. (Elsevier B.V., 2007)
Previous molecular dynamic simulations have reported elongation of the existing ß-sheet in prion proteins. Detailed examination has shown that these elongations do not extend beyond the proline residues flanking these ß-sheets. In addition, proline has also been suggested to possess a possible structural role in preserving protein interaction sites by preventing invasion of neighboring secondary structures. In this work, we have studied the possible structural role of the flanking proline residues by simulating mutant structures with alternate substitution of the proline residues with valine. Simulations showed a directional inhibition of elongation, with the elongation progressing in the direction of valine including evident inhibition of elongation by existing proline residues. This suggests that the flanking proline residues in prion proteins may have a containment role and would confine the ß-sheet within a specific length